Dying and Disabled Children : Dealing With Loss and Grief. - Dick, Harold M. (Taylor and Francis, 2014)
In this sensitive and compassionate look at terminally ill and disabled children, professionals from the medical community examine the stresses faced by their parents and siblings. They address the crucial element of communication--within a family and between health care providers and family members--in dealing with a child's serious illness. Ethical decision making, learning to recognize the child's suffering, and talking to children about death are honestly and clearly discussed. Experts offer direct interventions to help family members through the grieving process once a child has died.